Znanje in odnos do telemedicine med študenti zdravstvene nege in medicinskimi sestrami - Hvalič Touzery, Simona (Informatica Medica Slovenica, 2024)
Telemedicine is becoming an important part of healthcare but it is insufficiently integrated into the curricula for future nurses and nurses’ additional training. Nurses represent a large part of the healthcare workforce and are an important motivator for the use of telemedicine with patients. However, there is a knowledge gap regarding their attitudes towards telemedicine, their general knowledge of it, and their acceptance of and interest in using telemedicine. Even less is known about these topics from the perspective of nursing students. The aim of the study was to explore the knowledge, attitudes and interest in the use of telemedicine among Slovenian nurses and nursing students. The survey was conducted from September to December 2023 on a purposive sample of 478 nurses and nursing students. In general, the respondents rated their knowledge of telemedicine as low. A lack of training in telemedicine was identified. The results indicate the presence of technology-based and general ageism, which is more pronounced among students. There is a strong correlation between general attitudes towards telemedicine and interest in its use. The survey points to the need to include telemedicine-related content and technology-based ageism in the curricula for future nurses. This content should also be offered as additional training. Future research should further investigate the attitudes and acceptance factors of telemedicine in elder care.
Keywords: ageism; interes za uporabo; interest to use; Medicinska tehnologija; Medicinske sestre; nursing; starizem; Telemedicina; telemedicine; nursing; ageism, interest to use; telemedicinska obravnava; Zdravstvena nega